O13.5 Association between dietary intake and dysbiotic vaginal microbiota. (13th September 2015) - Tuddenham, SA; Rovner, AJ; Ma, B; Robinson, C; Gajer, P; Ravel, J; Ghanem, KG; Brotman, RM
Abstract : Background: Suboptimal nutrition has been associated with an increased risk of bacterial vaginosis (BV). In this study, we examined the association between dietary intake and BV-associated vaginal microbiota. Methods: We analysed the baseline visit of the Hormonal Contraception Longitudinal Study, a cohort of reproductive-aged women who reported at enrollment intentions to initiate or cease hormonal contraception (HC). Dietary intake was estimated using the Block Brief 2000 Food Frequency Questionnaire. Vaginal microbiota composition was assessed using 16S rRNA gene analysis and categorised based on the types and relative abundance of bacteria (termed community state types (CSTs)). Nutrients were categorised into quartiles and the associations between nutrients and CST-IV, a low- Lactobacillus CST, were evaluated by logistic regression. Separate models were built for each nutrient controlling for demographics, tobacco use, behavioural factors, HC and dietary variables (total energy intake, and where appropriate, percent of calories from fat, protein, carbohydrates). Results: A total of 98 women were included in this analysis. The mean age of the women was 25.9, mean body mass index was 27.9, 29.6% were African American and 47.9% were on HC at enrollment. 26.5% of women had a low relative abundance of Lactobacillus spp. (CST-IV). In adjusted multivariate analyses, the highest quartile of vitamin E (OR: 0.01, 95% CI: 0.001–0.26), zinc (OR: 0.03, 95% CI: 0.18–0.03) and magnesium (OR: 0.06, 95% CI: 0.004–0.75) intake were associated with reduced risk of carrying a low- Lactobacillus CST-IV state. Conclusion: Higher intakes of vitamin E, zinc, and magnesium were associated with a decreased risk of having a dysbiotic vaginal microbiota. These findings concur with prior studies that have reported magnesium and zinc deficiencies associated with recurrent bacterial infections and inflammation, and vitamin E (an antioxidant) with anti-inflammatory properties. Dietary interventions targeted at improving intake of select micronutrients may decrease the risk of bacterial vaginosis and its sequelae. Disclosure of interest statement: Funding for this study was provided by the National Institutes of Allergy and Infectious Diseases. No pharmaceutical grants were received in the development of this study.